1981
DOI: 10.1207/s15328023top0804_7
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Death Education Course on Participant Attitudes toward Death and Dying

Abstract: Three of four attitudinal changes were obtained by clarifying objectives and quantifying by the Semantic Differential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

1987
1987
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…Our project has shown how important it is to talk about death and how it produces beneficial effects on the psychological well-being of adolescents. According to the literature (Durlak & Riesenberg, 1991; Harrawood, Doughty, & Wilde, 2011; Knight & Elfenbein, 1993; Leviton, 1977; McClatchey & King, 2015; Mueller, 1976; Shoemaker, Burnett, Hosford, & Zimmer, 1981; Testoni, Ronconi, et al., 2018), meetings with qualified educators have led students to examine an often-avoided topic, increasing their understanding and familiarity. Addressing the issue of dying significantly reduced their fear of death, allowing them to face episodes of mortality salience in a more peaceful way.…”
Section: Discussionmentioning
confidence: 99%
“…Our project has shown how important it is to talk about death and how it produces beneficial effects on the psychological well-being of adolescents. According to the literature (Durlak & Riesenberg, 1991; Harrawood, Doughty, & Wilde, 2011; Knight & Elfenbein, 1993; Leviton, 1977; McClatchey & King, 2015; Mueller, 1976; Shoemaker, Burnett, Hosford, & Zimmer, 1981; Testoni, Ronconi, et al., 2018), meetings with qualified educators have led students to examine an often-avoided topic, increasing their understanding and familiarity. Addressing the issue of dying significantly reduced their fear of death, allowing them to face episodes of mortality salience in a more peaceful way.…”
Section: Discussionmentioning
confidence: 99%
“…Hemşireler bu eğitimle ölüm karşısındaki kaçınma davranışlarını fark etmişler ve bu davranışların ölen hastanın rahatlığını sağlamayı ve uygun bakım almasını engellediğini anlamış-lardır. [12,[24][25][26]28] Ölüm eğitimi, hemşirelerin hasta ve ailelerine etkili yaşam sonu bakım verebilmeleri için öncelikle kendi davranışlarına ilişkin içgörü kazanmasını sağ-lar. Bu eğitim sırasında hemşireler ölüm karşısında yaşadıkları duyguların kabul edilebilir ve evrensel olduğunu fark ederler.…”
Section: öLüm Kaygısı Ile Başetmede öLüm Eğitimiunclassified
“…These investigations have sometimes produced conflicting or inconclusive results. [6][7][8][9][10] Although several studies tested the relationship between demographic variables, such as gender, age, and attitude, studies on the relationship between personal experience in dealing with loss and attitude are limited. No studies were found that evaluated the relationship between attitude toward caring for terminally ill persons and religion, spiritual beliefs, or the lack of spiritual beliefs.…”
Section: Introductionmentioning
confidence: 99%